Assessing Genetic Diversity of Three Species of Potato Tuber Moths (Gelechiidae, Lepidoptera) in the Ecuadorian Highlands - Fu, Z.; Castillo Carrillo, C.I.; Rasheed, Awais; Asaquibay, C.; Aucancela, R.; Camacho, J.; López, V.; Quimbiamba, V.; Yumisaca, F.; Panchi, N.; Velasco, C. (Florida Entomological Society, 2020)
Three species of potato tuber moths, Tecia solanivora Povolny, Symmetrischema tangolias Gyen, and Phthorimaea operculella Zeller (all Lepidoptera: Gelechiidae), attack potato plants in the highlands of Ecuador and cause great economic losses. To understand their ecology and to develop precise integrated pest management strategies, a description of the molecular identification of each species and genetic diversity within populations is needed. In this study, we assessed the genetic diversity of a total of 112 moth samples of these 3 distinct species. Samples were collected from the 4 central provinces (Bolivar, Chimborazo, Cotopaxi, and Tungurahua) in the Ecuadorian highlands, where potato is a major crop for food security. Using polymerase chain reaction (PCR) and Sanger sequencing, we compared mitochondrial gene sequences among conspecific moth samples. Each of the 3 species exhibited different patterns regarding genetic diversity; more than 1 haplotype was present in P. operculella and S. tangolias, whereas all T. solanivora samples were found to be genetically identical. This initial effort of molecular characterization of the potato tuber moths will facilitate identifying incursion and potential migration route of Gelechiidae species as well as prevention of the pest outbreaks.